Quaternary structure effects on the hexacoordination equilibrium in rice hemoglobin rHb1: Insights from molecular dynamics simulations - Morzan, Uriel (2013)
Nonsymbiotic hemoglobins (nsHbs) form a widely distributed class of plant proteins, which function remains unknown. Despite the fact that class 1 plant nonsymbiotic hemoglobins are hexacoordinate (6c) heme proteins (hxHbs), their hexacoordination equilibrium constants are much lower than in hxHbs from animals or bacteria. In addition, they are characterized by having very high oxygen affinities and low oxygen dissociation rate constants. Rice hemoglobin 1 (rHb1) is a class 1 nonsymbiotic hemoglobin. It crystallizes as a fully associated homodimer with both subunits in 6c state, but showing slightly different conformations, thus leading to an asymmetric crystallographic homodimer. The residues that constitute the dimeric interface are conserved among all nsHbs, suggesting that the quaternary structure could be relevant to explain the chemical behavior and biological function of this family of proteins. In this work, we analyze the molecular basis that determine the hexacoordination equilibrium in rHb1. Our results indicate that dynamical features of the quaternary structure significantly affect the hexacoordination process. Specifically, we observe that the pentacoordinate state is stabilized in the dimer with respect to the isolated monomers. Moreover, the dimer behaves asymmetrically, in a negative cooperative scheme. The results presented in this work are fully consistent with our previous hypothesis about the key role played by the nature of the CD region in determining the coordination state of globins